Detection and measurement of artificial periapical lesions by cone‐beam computed tomography. (2nd July 2013) - Liang, Y.‐H.; Jiang, L.; Gao, X.‐J.; Shemesh, H.; Wesselink, P. R.; Wu, M.‐K.
Abstract Aim To test the ability of periapical radiography (PA) and cone‐beam computed tomography (CBCT) to determine the presence/absence of periapical lesions and examine the reliability of volumetric measurements of periapical lesions on CBCT scans. Methodology After tooth extractions in human mandibles, bone defects were cut at the base of extraction sockets to mimic periapical bone lesions. The teeth were then returned into the extraction sockets. Sixty‐three roots of anterior teeth, premolars and molars with artificial periapical lesions and 37 roots without lesions were examined with PA and CBCT. Presence/absence of periapical lesion was noted. The CBCT‐based volume of each lesion (Vct) was measured using Amira software 5.4 (Visage Imaging GmbH, Berlin, Germany). A replica of each lesion was created using silicone impression material, and the volume of the replica was measured using a water displacement method, representing the physical volume of the lesion (Vp). Regression analysis was used to test the correlation between the Vp and Vct values. Results The positive and negative predictive values and accuracy for CBCT in diagnosing periapical lesions were all 1, compared with 1, 0.64 and 0.79 for PA diagnosis. Twenty‐one (33%) lesions were undetected by PA. The Vp (21.5 ± 11.0 mm3) and Vct (21.4 ± 11.5 mm3) values of 63 lesions were highly correlated (R2 = 96.9%, P < 0.001). Conclusion Cone‐beam computed tomography is more accurate than PA in diagnosing periapical lesions associated with mandibular teeth. The volumes of artificial mandibular periapical lesions were accurately measured with CBCT data.